Constructing Historical Euro-Zone Data. - Doornik, J; Hendry, D; Beyer, A (Department of Economics (University of Oxford), 2000)
Existing methods of reconstructing historical Euro-zone data by aggregation of the individual countries' data raises numerous difficulties due to past exchange rate changes. The approach proposed here is designed to avoid such distortions, and aggregate exactly when exchange rates are fixed. In a simple 'Divisia-style' approach, we first compute growth rates within states, aggregate these, then cumulate this Euro-zone growth rate to obtain the aggregated levels variables. The aggregate of the implicit-deflator price index coincides with the implicit deflator of our aggregate nominal and real data. We investigate the properties of this growth-rate method for aggregation, and construct Euro-zone measures for M3, GDP and prices over the previous two decades.